Teaching International Students: Improving Learning for All - Griffith, Lauren Miller (Journal of International Students, 2011)
The fourteen contributors to this edited volume put forth a powerful concept. They argue that the struggles faced by international students in the classroom can be a barometer for the rest of our students, or, as the title of the first chapter puts it, “canaries in the coal mine.” Being attuned to the needs and difficulties of international students can often be an early alert system for the rest of the class.